2021
DOI: 10.1002/mmce.22734
|View full text |Cite
|
Sign up to set email alerts
|

Ground plane design configuration estimation of 4.9  GHz reconfigurable monopole antenna for desired radiation features using artificial neural network

Abstract: This paper presents a system based on artificial neural network (ANN) that predicts ground plane design for desired radiation properties of a monopole antenna with operation band of 4.8 to 5 GHz. The operating frequency can be adapted to any other frequency regimes. Initially, a 180 Â 180 mm2 ground plane, which is composed of a copper layer, is designed and integrated to a radiative pole that creates monopole antenna configuration. The ground plane is divided into 18 rows and 18 columns as 18 Â 18 matrix so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In recent years, various MMAs have been extensively proposed. Compared with traditional absorbing materials, MMAs show many better advantages, such as almost perfect absorption, thinner thickness, wider absorption bandwidth, 24,25 and radar cross‐section (RCS) reduction 26–29 . However, due to the darker color of the molding material, most MMAs are opaque, hindering their development as transparent EMI shielding windows 30–33 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various MMAs have been extensively proposed. Compared with traditional absorbing materials, MMAs show many better advantages, such as almost perfect absorption, thinner thickness, wider absorption bandwidth, 24,25 and radar cross‐section (RCS) reduction 26–29 . However, due to the darker color of the molding material, most MMAs are opaque, hindering their development as transparent EMI shielding windows 30–33 .…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterial is widely used in stealth technology, antenna design, and other fields 1–3 . The unusual effects do not necessarily imply the use of the volumetric (3D) metamaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterial is widely used in stealth technology, antenna design, and other fields. [1][2][3] The unusual effects do not necessarily imply the use of the volumetric (3D) metamaterials. You can also manipulate the electromagnetic (EM) wave with the help of two-dimensional (2D) structuresso-called metasurfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Reconfigurable metasurfaces and reconfigurable antennas are also hot topics. 7,8 Phase gradient metasurface (PGMS) is a novel metasurface proposed by Yu et al, 9 and demonstrated the generalized Snell's law. The so-called PGMS refers to the gradient distribution of the phase shift.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials also have extensive applications in microwave imaging and antenna decoupling 4–6 . Reconfigurable metasurfaces and reconfigurable antennas are also hot topics 7,8 . Phase gradient metasurface (PGMS) is a novel metasurface proposed by Yu et al, 9 and demonstrated the generalized Snell's law.…”
Section: Introductionmentioning
confidence: 99%